Manajemen Inovasi Pembelajaran Adaptif di Era Disrupsi, Systematic Literature Review - Puput Puspito Rini (Jurnal Ilmiah Pendidikan dan Keislaman, 2024)
Adaptive learning innovation management lies at the intersection of management science, educational technology, and contemporary pedagogy, encompassing the planning and control of learning systems that effectively respond to learner diversity in the 21st century.This research aims to comprehensively examine adaptive learning innovation management in the era of disruption through four key dimensions: AI technology and adaptive systems, innovative leadership, holistic learning models, and system resilience in a complex and evolving environment.The method used is a Systematic Literature Review (SLR), conducted systematically, transparently, and replicably to map the development of adaptive learning innovation management studies and minimize bias in the collection and interpretation of scientific literature.The review of ten articles yielded four main categories: AI technology and adaptive systems as a foundation for learning transformation, innovative leadership and management strategies, holistic integrative adaptive learning models, and system resilience and adaptive management in complex collaborative environments based on a generative systemic perspective.The study concluded that AI integration enhances personalization and efficiency of education sustainably, adaptive entrepreneurial leadership becomes a prerequisite for organizational innovation, a holistic approach based on complexity theory enhances learner capacity, and system resilience is determined by quality governance and inter-organizational learning that enables generative responses to disruption.